PENGARUH UMUR DAN PENGALAMAN BERINVESTASI TERHADAP HUBUNGAN ANTARA FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI PENGGUNAAN WEBSITE PERUSAHAAN PUBLIK - Purbandari, Theresia (Widya Warta, 2010)
Public company's website can be interpreted as a medium of promotion or presentation which includes all the official information about the company. The information presented is in the form of information of finance, business, and corporate sustainability. This website provides a menu of investor relations, which contains the information that is important for companies to maintain relationship with investors or attract investors to invest. The purpose of this study was to test empirically the factors associated with the acceptance and the use of public company’s website by individual investors in the investment decision-making process. The model used in this study was UTAUT (Unified Technology and Acceptance Theory) model. The respondents in this research were 102 individual investors who had an account for buying and selling shares through the securities companies. The data analysis was performed by the use of PLS (Partial Least Square) method. The result of the data analysis showed that the research could not prove that age moderated the relationship between performance expectancy and the intention to use the public company's website. Moreover, it could not prove that the investing experience moderated the relationship between effort expectancy as well as social influences and the intention to make use of the public company's website.